A biased fossil record can preserve reliable phylogenetic signal. Issue 3 (August 2022) - Woolley, C. Henrik; Thompson, Jeffrey R.; Wu, Yun-Hsin; Bottjer, David J.; Smith, Nathan D.
Abstract: The fossil record is notoriously imperfect and biased in representation, hindering our ability to place fossil specimens into an evolutionary context. For groups with fossil records mostly consisting of disarticulated parts (e.g., vertebrates, echinoderms, plants), the limited morphological information preserved sparks concerns about whether fossils retain reliable evidence of phylogenetic relationships and lends uncertainty to analyses of diversification, paleobiogeography, and biostratigraphy in Earth's history. To address whether a fragmentary past can be trusted, we need to assess whether incompleteness affects the quality of phylogenetic information contained in fossil data. Herein, we characterize skeletal incompleteness bias in a large dataset (6585 specimens; 14, 417 skeletal elements) of fossil squamates (lizards, snakes, amphisbaenians, and mosasaurs). We show that jaws + palatal bones, vertebrae, and ribs appear more frequently in the fossil record than other parts of the skeleton. This incomplete anatomical representation in the fossil record is biased against regions of the skeleton that contain the majority of morphological phylogenetic characters used to assess squamate evolutionary relationships. Despite this bias, parsimony- and model-based comparative analyses indicate that the most frequently occurring parts of the skeleton in the fossil record retain similar levels of phylogenetic signal as parts of the skeleton that are rarer. These results demonstrate that the biased squamate fossil record contains reliable phylogenetic information and support our ability to place incomplete fossils in the tree of life.